Marketing Strategy in Dental Practices: A Scoping Review Study - Juliawati, Mita; Juslily, Marta; Fathiah, Khalda; Emily, Laura; Aurelius, Thomas; Budiono, Jessica (Indonesian Dental Association, 2023)
Introduction: Knowledge and skills required for a dentist to be able to manage dan promote their dental practice are not only clinical skills but also managerial skills. One of which is the marketing and its strategy. Marketing need to be implemented in dental services. Objective: To determine the marketing strategies in dental services. Method: The research design used for this manuscript is literature the review. The selection criteria for the articles are experimental and cross-sectional studies. Articles were obtained using electronic databases Google Scholar with the keywords